(untitled) (Edugama: Jurnal Kependidikan dan Sosial Keagamaan, 2021)
Organizational performance variable is an important variable in management studies including education management. Assessment or measurement of organizational performance aims to provide an overview of how the process of achieving organizational goals and quality is realized. This variable has occupied an important position in every study and institutional (management) research. Many researchers are interested in assessing organizational performance from various perspectives. The impact can be seen in the variations of the use of dimensions and indicators in exploring research data. Dimensions such as; effectiveness-efficiency, focus on processes, structural transformation, teamwork and strategy are dimensions often used by researchers in assessing organizational performance. Organizational performance is not an independent variable, but is related to or influenced by other organizational variables such as; leadership, management systems, commitment and culture.